We find inverse in two scenarios

- When f is given as set
- When f is given as a function

####
**
When f is given as set
**

####
**
f = {(1, 4), (2, 5), (3, 6)}
**

In f
^{
-1
}
,

We reverse all the elements

(1, 4) becomes (4, 1)

(2, 5) becomes (5, 2)

(3, 6) becomes (6, 3)

∴ f
^{
-1
}
= {(4, 1), (5, 2), (6, 3)}

####
**
When f is given as
**

####
**
f(x) = 2x + 1
**

We put f(x) = y

and find y in terms of x

f(x) = 2x + 1

y = 2x + 1

y – 1 = 2x

2x = y – 1

x = (y - 1)/2

∴ f
^{
-1
}
= (y - 1)/2

To summarise